PENDAMPINGAN PENERAPAN MANAJEMEN PENJADWALAN DALAM OPTIMALISASI PROSES PEMBELAJARAN - Supriana, I.W.; Putri, L.A.A.R.; Giri, G.A.V.M.; Darmawan, I.D.M.B.A. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i01.p04, 2023)
Scheduling learning activities is a routine activity every semester which is complicated and requires high accuracy. If the scheduling process is carried out inaccurately, there will be many implementation conflicts. In addition, learning scheduling must be completed on time so that the learning process can run according to the specified time. Likewise the scheduling process carried out at the Margarana Tourism Vocational School which has limited study space with a large number of subjects at all levels carried out each semester, this makes it difficult to maximize the use of classrooms. Through the Udayana Serving Program, assistance is provided for the management of the room arrangement system which can optimize the use for teachers of the Margarana Tourism Vocational School. The method of implementing community service is carried out by socialization, lectures, discussions and workshops in the form of training in the application system for setting up learning spaces. Evaluation results based on the implementation of the service program on testing the usability component of the system, that on average participants stated 58.67% agreed and 16% strongly agreed. Meanwhile, in the management application system standard test, 60% agreed and 20% strongly agreed. Based on the evaluation results, participants are able to understand and apply scheduling management, the scheduling system provides access for each teacher to set their own schedule and the leader can approve schedule submissions through the system. Keywords: Scheduling, Room, Vocational School, Learning Proces